Implications of Health Care Providers by Physicians' and Pharmacists' Attitudes and Perceptive Barriers towards Interprofessional Collaborative Practices - Anmar Al-Taie (Universidade de São Paulo, 2023)
Abstract The study was aimed at assessing and comparing physicians' and pharmacists' attitudes and experiences with collaborative practices, along with the extent of barriers toward interprofessional collaboration in Iraqi healthcare settings. A descriptive, cross-sectional study was conducted among physicians and pharmacists in different healthcare settings in Baghdad, Iraq through an interview using a structured 3-part questionnaire, assessing the demographic characteristics, attitudes and barriers to interprofessional collaborative practices. A total of 384 participants were enrolled in this study. The physicians and pharmacists reported a significant positive attitudes towards collaboration, such as ''pharmacists are qualified to assess and respond to patients' drug treatment needs'' (69.8%, vs. 89.6%,; P=0.001);''pharmacists have special expertise in counseling patients on drug treatment'' (59.9%, vs. 86%; P=0.001); ''physicians and pharmacists should be educated to establish collaborative relationships'' (80.7%, vs. 100%; P=0.001), respectively. However, 57.3% of the physicians agreed about ''lack or inadequate of pharmacists' time to provide direct and effective patient care because of medications dispensing duties'', while 56.8% of the pharmacists disagreed about this barrier (P=0.005). Both professions reported significant, positive attitudes and shared some barriers toward collaborative practices; however, there is a disagreement in some areas in which both professions would like more collaboration for better patient care.